Optical coherence tomography based particle image velocimetry (OCT-PIV) of polymer flows. (June 2015) - Buchsbaum, A; Egger, M; Burzic, I; Koepplmayr, T; Aigner, M; Miethlinger, J; Leitner, M
Abstract: The measurement of spatially resolved velocity distributions is crucial for modelling flow and for understanding properties of materials produced in extrusion processes. Traditional methods for flow visualization such as particle image velocimetry (PIV) rely on optically transparent media and cannot be applied to turbid polymer melts. Here we present optical coherence tomography as an imaging technique for PIV data processing that allows for measuring a sequence of time resolved images even in turbid media. Time-resolved OCT images of a glass-fibre polymer compound were acquired during an extrusion process in a slit die. The images are post-processed by ensemble cross-correlation to calculate spatially resolved velocity vector fields. The results compared well with velocity data obtained by Doppler-OCT. Overall, this new technique (OCT-PIV) represents an important extension of PIV to turbid materials by the use of OCT. Highlights: Optical coherence tomography is applied as an imaging technique for particle image velocimetry. The applicability of optical coherence tomography for flow visualization in turbid media is demonstrated. We measure flow profiles in a fiber-reinforced polymer extrusion process with high spatial resolution. Results from OCT based PIV compare well to data obtained by Doppler-OCT.